2017
DOI: 10.1080/02699052.2017.1374468
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury amongst indigenous people: a systematic review

Abstract: Published studies demonstrate that Indigenous people have a higher prevalence or incidence of TBI compared to non-Indigenous people. Limited studies explore culturally appropriate rehabilitation and intervention methods and Indigenous understandings of TBI. It is imperative that future research consider the nature and efficacy of culturally appropriate approaches and their contribution towards better outcomes for Indigenous people with TBI, and their families and communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…In addition, the occurrence of TBI in NSW residents identifying as Aboriginal and Torres Strait Islander was 1.7 times the rate of the general population. This finding, supporting known ethnicity‐related disparities in TBI risk, 30 allows for a more accurate estimate of the magnitude of risk among Aboriginal and Torres Strait Islander peoples. There are only two studies providing data in this regard but these are limited to small, selected Australian cohorts, such as assault‐related TBI 12 and incarcerated young people 31 …”
Section: Discussionsupporting
confidence: 66%
“…In addition, the occurrence of TBI in NSW residents identifying as Aboriginal and Torres Strait Islander was 1.7 times the rate of the general population. This finding, supporting known ethnicity‐related disparities in TBI risk, 30 allows for a more accurate estimate of the magnitude of risk among Aboriginal and Torres Strait Islander peoples. There are only two studies providing data in this regard but these are limited to small, selected Australian cohorts, such as assault‐related TBI 12 and incarcerated young people 31 …”
Section: Discussionsupporting
confidence: 66%
“…However, none of the studies reviewed principally sought to investigate the transitional experiences of Indigenous Australians. A recent comprehensive systematic review of research focusing on TBI among Indigenous people generally found that almost half the studies were focused not on transition but on prevalence or incidence rate only (Lakhani, Townsend & Bishara, 2017). In health care generally, research indicates that Indigenous Australians experience differences in the health care they receive in hospital (Australian Health Ministers' Advisory Council, 2012;Paradies, Harris & Anderson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Changes related to social adjustment may not be immediately apparent but may continue to emerge over time (Olver, Ponsford & Curran, 2009;Salas, Casassus, Rowlands, Pimm & Flanagan, 2018), with personal and social circumstances like age, gender, incidence of depression and family support impacting on recovery, although to varying degrees (Alway, Gould, Johnston, McKenzie & Ponsford, 2016;Gauthier et al, 2018;Lewis & Horn, 2017;O'Reilly, Wilson & Peters, 2018). However, the overarching cultural context of the brain injury survivor, particularly that related to minority peoples with a history of colonisation and discrimination, has rarely been referred to in the research literature (see recent systematic review by Lakhani, Townsend and Bishara (2017)), despite profoundly influencing a person's recovery journey in significant ways, including access to services. In an Aboriginal 1 world view, for example, and consistent with Bronfenbrenner's socioecological model (1979), the individual is embedded in the family and community in a collectivist context, so that the effects/experience of a brain injury have immediate relevance and ramifications for that person's immediate and extended family, community and beyond, as well as for the person him/herself (see Fig.…”
Section: Introductionmentioning
confidence: 99%